2018
DOI: 10.7897/2230-8407.098177
|View full text |Cite
|
Sign up to set email alerts
|

Aquasomes as a Carrier System for Oral Delivery of Bromelain

Abstract: The aim of the present study was to investigate the aquasome as potential carriers for efficient oral delivery of Bromelain in order to improve its bioavailability. Aquasomes prepared by inorganic core of calcium phosphate covered with a sugar film and further adsorption of the Bromelain and characterized in terms of the morphological examination, particle size distribution, entrapment efficiency, drug loading and in vitro release. The surface morphology of the freeze-dried aquasomes were smooth, discrete with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The interest to develop a carrier for bromelain can be expressed by the high number of the published studies; thus, there have been reported the obtaining of bromelain capped gold nanoparticles [12] and the development of aquasomes for its oral delivery [13]. A bacterial cellulose membrane containing bromelain was presented in the literature [2]; the authors found that their carrier can improve the antimicrobial activity 9 times than the pure substance.…”
Section: Introductionmentioning
confidence: 99%
“…The interest to develop a carrier for bromelain can be expressed by the high number of the published studies; thus, there have been reported the obtaining of bromelain capped gold nanoparticles [12] and the development of aquasomes for its oral delivery [13]. A bacterial cellulose membrane containing bromelain was presented in the literature [2]; the authors found that their carrier can improve the antimicrobial activity 9 times than the pure substance.…”
Section: Introductionmentioning
confidence: 99%
“…(50) successfully immobilized DNAase (therapeutic enzyme) on the surface of the aquasomes and was able to target the specific site of action and to bring about a prominent therapeutic effect as desired. Bromelain multi-particulate drug carrier for oral delivery (53) Hepatitis B Vaccine Antigen for prevention of jaundice (36) Haemoglobin carrier for oxygen (26) Merozoite Surface Protein-119 (MSP-119)…”
Section: Fundingmentioning
confidence: 99%
“… Aquasomes Trilayered self-assembled nanostructures comprising a solid phase nanocrystalline. Bromelain Lack of in vivo data [ 101 ] Archaeosomes Vesicles composed of glycerolipids of archaea with potent adjuvant activity. Ovalbumin Enhancement in oral immunization [ 102 ] Colloidosomes Hollow shell microcapsules consisting of coagulated or fused particles at the interface of emulsion droplets Insulin Improvement in hypoglycemic effect [ 103 ] Cryptosomes Stealth liposomes or immune-liposomes with a surface coat of PEG or its derivatives.…”
Section: Introductionmentioning
confidence: 99%